Exegetical and Legal Analysis of the Verse “and Women Shall Have Rights Similar to the Rights Against Them, …; but Men Have a Degree (of Advantage) Over Them” - Mahdi Mehrizi (آموزه‌‌های فقه مدني)
This article attempts to analyze this verse “and women shall have rights similar to the rights against them, according to what is equitable; but men have a degree (of advantage) over them”, firstly to answer the apparent incompatibility of the top and the bottom of this verse and then to propound it as a general rule and a norm for equality of women and men rights and duties. The writer says that if there are flagrant and impressive differences between their rights and duties, the process of ijtihad and understanding of rights and duties must be reconsidered especially where it is terminated with the evidence of ijtihad and understanding of hadith and traditions.